Construction of International Cooperation strategies: An inquiry into the learning experience - Cabeza-Pulles, Dainielis; Coral-Guerrero, Carmen Amelia (Iberoamerican Journal of Development Studies, 2016)
The present research is the product of a collection of primary information in the context of the formulation of the International Cooperation strategy of the Municipality of Pasto, for the purpose of determining the path of construction of this process, its impact and challenges and, above all, the learning achieved through the participatory formulation of the International Cooperation strategy. The methodology of the research is of a qualitative interpretative study, which allowed to rebuild from the sight of actors the participatory formulation of the strategy of International Cooperation, rescuing the importance of participation in all levels, recognizing the team working and the generation of partnerships, trust and commitment in the pursuit of strengthening and sustainability of the process of internationalization of the Municipality. Finally, the research concluded with a series of reflections concerning the formulation of strategies for International Cooperation.